Redox-active phthalocyanine-decorated graphene aerogels for high-performance supercapacitors based on ionic liquid electrolyte. Issue 41 (19th October 2020) - Yang, Lifang; Zhuo, Kelei; Xu, Xiaochao; Zhang, Zezhong; Du, Quanzhou; Chen, Yujuan; Sun, Dong; Wang, Jianji
Abstract : CuPC-rGA and PC-rGA are prepared to match an ionic liquid electrolyte. The IL-based pseudocapacitance system shows a superior energy-power performance. Abstract : Ionic liquids (ILs) with a wide potential window have shown great potential in the fabrication of high-energy supercapacitors (SCs). However, developing pseudocapacitive material-matching IL electrolytes for further incorporating their energy-storing advantages is still a great challenge. Herein, we demonstrated the one-step hydrothermal synthesis of phthalocyanine (PC) and copper(ii ) phthalocyanine (CuPC)-functionalized reduced graphene oxide aerogels (PC-rGA and CuPC-rGA, respectively). PC and CuPC with a nitrogen-containing π-conjugated macrocyclic structure and redox activity were anchored on the surface of graphene sheets via π–π interactions, and thus PC-rGA and CuPC-rGA could match imidazolium IL electrolytes and provide pseudocapacitance, exhibiting an enhanced specific capacitance of 192 F g −1 and 201 F g −1 at 1 A g −1, respectively. Moreover, the symmetric SCs assembled using the aerogels delivered a high energy density of 111 W h kg −1 at a power density of 1009 W kg −1 for CuPC-rGA, and 107 W h kg −1 at 1000 W kg −1 for PC-rGA.